Preliminary Computational Analysis of Pyrazinamide-Based Derivatives Reveals Possible Inhibition of SARS-CoV-2 RNA-Dependent RNA Polymerase, and Their Possible Use as Antiviral Agents - Anukanon, Shisanupong; Teerapattarakan , Narudol (Trends in Sciences, 2022)
Pyrazinamide is a pyrazine analog currently used to treat tuberculosis. It shares a core structure similar to that of favipiravir, which is a promising drug candidate that may inhibit the SARS-CoV-2 RNA-dependent RNA polymerase. This feature could be an opportunity for further drug development of anti-COVID-19 medication starting from a pyrazinamide core structure. This study aimed to determine and predict the most effective pyrazinamide-based analogs against the SARS-CoV-2 RNA-dependent RNA polymerase by using combined ligand- and structure-based computational analysis. This study performed a rational in silico study to screen pyrazinamide-like molecules from a commercially available ZINC database, with a similarity score higher than 0.40, and then these screened for acceptable pharmacokinetic properties, and then to further conduct molecular docking analysis with SARS-CoV-2 RNA-dependent RNA polymerase. The results showed that compound 12, having a dichloropyrimidine core structure had a similarity score of 0.446. It exerted the most binding affinity with RNA-dependent RNA polymerase, with estimated docking scores of −5.72, −5.25, −7.06, −7.00 and −4.63 kcal/mol in intact, ribosylated, mono-phosphoribosylated, di-phosphoribosylated and tri-phosphoribosylated forms, respectively. Watson-Crick base-pairing of compound 12 indicated that it favored binding with the uracil nucleoside of the RNA template. Compound 12 was confirmed as the lead compound, being a pyrazinamide-like molecule, and so might be a most promising candidate molecule, as an adenine analog RNA-dependent RNA polymerase inhibitor. It is suggested that the antiviral effect of this lead compound should be studied further as part of a drug discovery and development process. HIGHLIGHTS In silico analysis was performed to screen pyrazinamide-like compounds against the RNA-dependent RNA polymerase Pharmacokinetics and drug-likeliness properties of fourteen preselected compounds were assessed by using SwissADME with favorable results Among these preselected compounds, compound 12 showed the best docking score in almost all of its phosphoribosylated forms GRAPHICAL ABSTRACT